Geometric error identification and compensation for rotary worktable of gear profile grinding machines based on single-axis motion measurement and actual inverse kinematic model. (January 2021) - Xia, Changjiu; Wang, Shilong; Wang, Sibao; Ma, Chi; Xu, Kai
Highlights: A single-axis motion measurement based PDGEs identification method for rotary axes. The actual IKM based compensation method is presented for the PDGEs of rotary axes. The influence of the PDGEs of the worktable on the gear grinding errors is analyzed. Geometric accuracy tests of the worktable validated the compensation effectiveness. Abstract: Gear profile grinding accuracy is often restricted by geometric errors of the rotary worktable. This paper proposes a novel approach to improve the geometric accuracy of the worktable based on single-axis motion measurement and the actual inverse kinematic model (IKM). The volumetric error model of gear profile grinding machines is first established based on homogeneous transformation matrices (HTMs) and machine kinematic chains, and the actual IKM based compensation method is then proposed to offset the position-dependent geometric errors (PDGEs) of the worktable. It directly gives explicit analytical expressions of compensated motion commands for efficient compensation. Besides, a novel PDGEs identification approach based on single-axis motion measurement with a double ball bar (DBB) is presented for the worktable. This approach has improved identification accuracy and stronger robustness as the interference error of non-targeted axes is avoided. The influence of the installation errors of the workpiece ball on measurement results and the PDGEs on gear grinding errors were discussed. The experiments verified the effectiveness of the identification approach, and the geometric accuracy tests of the worktable validated the compensation method. Graphical abstract: Image, graphical abstract